PENGARUH PEMBERIAN MULSA DAN BEBERAPA JENIS PUPUK DAUN TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TERUNG (Solanum melongena L.) - Istiqomah Istiqomah; Ana Amiroh; Choirul Anam; Nur Fauziah Hasyim (AGRORADIX : Jurnal Ilmu Pertanian, 2023)
Eggplant is a type of vegetable that is used as an ingredient in vegetables or fresh vegetables. The nutritional content of eggplant is very high, especially the content of vitamin A and phosphorus. However, eggplant productivity has decreased along with the lack of nutrients absorbed. Therefore, mulch and foliar fertilizer are the right innovations to be applied to support the eggplant. The existence of mulch to suppress the growth of weeds and the availability of nutrients N, P, and K in the soil. The purpose of this study was to determine the application of mulch and foliar fertilizer to the growth and production of eggplant plants. This research was conducted in Banjarejo Village, Kedungpring District, Lamongan Regency. This study used a Randomized Block Design (RAK) with a factorial pattern with 3 replications, consisting of 2 factors, namely: type of mulch (M) and leaf fertilizer (D). The first factor consisted of 3 types of mulch, namely: no mulch (M0), straw mulch (M1) and silver black plastic mulch (M2). The second factor of foliar fertilizer consisted of 3 levels, namely: growmore foliar fertilizer (D1), mamigro foliar fertilizer (D2), and gandasil D (M3) leaf fertilizer. Based on the results of the study, it was concluded that the application of mulch and foliar fertilizers on the growth and production of eggplant plants had an interaction between the treatment of mulch and foliar fertilizers on plant height (42 DAP), fruit diameter, plant weight, and fruit weight per hectare at the age of 77 DAP. The application of black silver plastic mulch and mamigro leaf fertilizer got the best results on the parameters of plant height, fruit diameter, plant weight and fruit weight per hectare.